Measuring the Progress on Palm Oil Industrial Estate, Sumatera Corridor (MP3EI) - Jahrizal, Jahrizal; Dahliyusmanto, Dahliyusmanto; Marhadi, Marhadi; Setiawan, Denni (Program Pascasarjana, Universitas Riau, 2016)
The purpose of this study is to measure the progress of developing the Palm Oil Industrial Estate, sumatera corridor (MP3EI). This study conducted because Industrial Park has been developed almost 10 years laready but the progress is still slow. This study analyzed the characteristics of each variables of its resources on an Industrial Park. Dumai Industrial Park is chosen as a sample. Resources Based view theory is apllied to searching the weaknes and strength of the variables. There are 7 (seven) resources based : Human resources, financial resources, phisical and location resources, natural resources, technology resources, organisation resources, and inovation resources. Each variables is devided into indicators. Then, every indicators is formulated to get the index number. Having index numbers, the web approach is using to analyze the result. The findings are:1. Eventhought the raw material resources is very atractive variable in this industrial park,, but the organization resources has the lower index ( 0) .2. it means that the local government has reluctancy to develop the Tenayan Industrial Resources. Although the other resources have good index, but they are meaningless for Tenayan Industrial development. 3. it shows that Industrial Park at Kawasan Industri Dumai has a weakness to attract the tenant in to its location.